(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This paper aims to analyze the opinions held about virtual learning in the social sciences and whether its results tend to be positive or negative and their reasons. Methodology: a bibliographic review was carried out in search engines such as Google Scholar and various databases and indexed journals such as Scielo, Redalyc and Dialnet. Results: Ten articles published in the period between 2019 and 2023 are analyzed, 100% of the documents reviewed are in Spanish. Among the main findings it is observed that the inclusion of digital media for the learning of social sciences is favored to a large extent but there are certain limitations in terms of implementation, updating and development of the same as well as the little interest of the student. Conclusions:It is concluded that ICT is a valuable resource for the area of social sciences, provided that they are used with pedagogical criteria, adapted to the context and the needs of the students.It is recommended to continue researching on the best practices to integrate ICT in this area of knowledge, as well as to promote the continuous training of teachers and the development of digital skills in students.